Analisis Mitigasi Nonstruktural Bencana Banjir Luapan Danau Tempe - Musdah, Erwin; Husein, Rahmawati (Universitas Muhammadiyah Yogyakarta, 2014)
This research aimed to know how mitigasi non-structural Tempe lake overflow flood disaster through ordering roomand to express cooperations inter-government regency in mitigasi non-structural Tempe lake overflow flood disasterthrough ordering room. This research is descriptive qualitative research with triangulation method data collection. Itso happens data analysis method used namely descriptive qualitative data analysis method. Result research indicatethat mitigasi non-structural effort Tempe lake overflow flood disaster through ordering room has look in some articlein lay-out plan regional policy area in Sidenreng Rappang, Soppeng and Wajo regency although inside regulation thatis same still found articles that are potentially detain that effort. Besides, this research found that do not have cooperationamong each one government regency in mitigasi non-structural through ordering room.